Self-healing high-toughness concrete and preparation method thereof

By using excessive precursor alkali in concrete to stimulate gelling systems and mixed fibers, the self-healing and toughness enhancement of concrete is achieved, solving the high cost of concrete crack control and repair in the prior art, and improving the mechanical properties and service capabilities of concrete.

CN119409453BActive Publication Date: 2025-03-28GUANGDONG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510012754.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-03-28
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

In the prior art, concrete is prone to cracks during use, existing control and repair methods are expensive and cannot control and repair cracks at the same time, and the repair effect is not ideal.

Method used

By using excessive precursor alkali in concrete to stimulate the gelling system, combined with mixed fibers, the self-healing and toughness enhancement of concrete can be achieved.

Benefits of technology

The low-cost preparation of concrete is achieved, integrating control and repair, improving the mechanical properties and service capabilities of concrete, with tensile strength reaching above 8.9MPa, compressive strength reaching above 100MPa, and the self-healing rate in 28 days reaches 98%, and the mass loss rate after 50 freeze-thaw cycles is only 0.66%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409453B_ABST
    Figure CN119409453B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of building materials, and more specifically, relates to a self-healing high-toughness concrete and a preparation method thereof, and in particular to a method for realizing self-healing of high-toughness concrete by using an excess precursor alkali-activated cementitious system, realizing self-repair of concrete after cracking by over-configuring the precursor of cementitious materials, and combining mixed fibers to enhance the toughness of concrete, thereby realizing low-cost configuration of concrete and a new type of self-healing concrete that integrates control and repair. When the mix ratio of the polymer precursor is 900 parts, the tensile strength of the concrete can reach more than 8.9MPa, the compressive strength can reach more than 100MPa, the self-healing rate of the concrete can reach 98% in 28 days, and the mass loss rate after 50 freeze-thaw cycles is only 0.66%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and more specifically relates to a self-healing high-toughness concrete and a preparation method thereof. Background Art

[0002] In current existing projects, concrete is prone to cracking. In order to prevent the cracks from expanding during the use of the building, concrete needs to be controlled or repaired at an early stage. For crack control, the commonly used method is to add different types of fiber materials or other additives to improve the overall toughness of concrete and control the further generation of cracks. In terms of repair, self-repair is currently mainly achieved through microbial, chemical or physical mechanisms. Microbial repair has high requirements on the type and living environment of microorganisms. Chemical repair requires the addition of expensive healing agents to form fillers with components in concrete, while physical mechanisms have high requirements for the pouring of concrete.

[0003] At present, the existing technologies for controlling and repairing cracks are all costly and cannot achieve the problem of controlling and repairing cracks at the same time. In addition, the repair effect of the current concrete with repair function cannot meet expectations, and various performance indicators have not been significantly improved. Summary of the invention

[0004] The purpose of the present invention is to provide a self-healing high-toughness concrete and a preparation method thereof, and more specifically to provide a method for realizing self-healing of high-toughness concrete by utilizing an excess precursor alkali-activated cementitious system, wherein self-repair of concrete after cracking is realized by over-configuring the precursor of the cementitious material, and the toughness of the concrete is enhanced by combining mixed fibers, so as to solve the problems existing in the above-mentioned prior art, realize low-cost preparation of concrete and a new type of self-healing concrete integrating control and repair.

[0005] To achieve the above object, the present invention provides the following solutions:

[0006] One of the technical solutions of the present invention is to provide a self-healing high-toughness concrete, wherein the raw materials include, by weight: 700-1100 parts of geopolymer precursor, 28.5 parts of sodium hydroxide solution, 306.6 parts of water glass, 543 parts of medium sand, 362 parts of fine sand, 95 parts of crushed rubber, 17 parts of PE fiber, 2.4 parts of PP fiber and 117.1 parts of water.

[0007] Furthermore, the geopolymer precursor includes blast furnace slag, fly ash and silica fume.

[0008] Optionally, the mass ratio of blast furnace slag, fly ash and silica ash is (530~850):(120~210):(30~60).

[0009] Optionally, the mass ratio of blast furnace slag, fly ash and silica ash is 535.1:129.9:35.

[0010] Optionally, the mass ratio of blast furnace slag, fly ash and silica ash is 611.6:148.4:40.

[0011] Optionally, the mass ratio of blast furnace slag, fly ash and silica ash is 688:167:45.

[0012] Optionally, the mass ratio of blast furnace slag, fly ash and silica ash is 764.4:185.6:50.

[0013] Optionally, the mass ratio of blast furnace slag, fly ash and silica ash is 840.9:204.1:55:28.5.

[0014] Furthermore, the concentration of the sodium hydroxide solution is 14 mol / L.

[0015] Furthermore, the average particle size of the crumb rubber is 0.32 mm.

[0016] The second technical solution of the present invention is to provide a method for preparing the self-healing high-toughness concrete, the steps comprising:

[0017] After fly ash, blast furnace slag and silica fume are evenly mixed, crushed rubber, medium sand and fine sand are added and stirred evenly, then sodium hydroxide solution, water glass and water are added and stirred evenly, and finally PE fiber and PP fiber are added and stirred evenly to obtain the self-healing high-toughness concrete.

[0018] The self-healing high-toughness concrete prepared by the present invention can be used for a long time without replacement or maintenance after one-time construction. The use of an over-proportioned amount of geopolymer precursors is very critical. The content of geopolymer precursors can directly affect the reaction rate and healing effect of self-healing of concrete after cracking. By reasonably adjusting the proportion of the precursors, the high-toughness concrete can be given the best healing effect.

[0019] The present invention discloses the following technical effects:

[0020] The invention realizes the high-toughness self-healing property of concrete by adding excess geopolymer precursor.

[0021] The present invention is based on a special over-preparation method of geopolymer concrete, which gives geopolymer concrete the ability to self-heal, and combines mixed fibers to improve the toughness of the original geopolymer concrete, enhance the crack control ability of geopolymer concrete, and combine the self-healing effect after cracking to effectively improve the mechanical properties and service capacity of concrete materials. When the mix ratio of the geopolymer precursor is 900 parts, the tensile strength of the concrete can reach more than 8.9MPa, the compressive strength can reach more than 100MPa, the 28-day concrete self-healing rate can reach 98%, and the mass loss rate after 50 freeze-thaw cycles is only 0.66%. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0023] Figure 1 It is a schematic diagram of the preparation process of the self-healing high-toughness concrete of the present invention;

[0024] Figure 2 The dimensions of the cube and dog bone specimens prepared in the experimental example;

[0025] Figure 3 It is a particle size distribution curve diagram of the raw materials used in the present invention;

[0026] Figure 4 Schematic diagram of the crack width and 28-day overall repair rate of the specimens of Examples 1 to 5 at different curing times. DETAILED DESCRIPTION

[0027] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0028] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0029] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0030] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0031] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0032] Unless otherwise specified, "parts" in the present invention refer to parts by mass.

[0033] The raw materials and reagents used in the present invention are all commercially available products.

[0034] In the specific implementation scheme of the present invention:

[0035] The fly ash is Class F fly ash (FA), with a specific gravity of 2.12 g / cm 3 , fineness value is 4000 cm 2 / g;

[0036] The specific gravity of blast furnace slag (GGBS) is 2.88 g / cm 3 , the fineness value is 3800 cm 2 / g;

[0037] The specific gravity of silica fume (SF) is 2.30 g / cm 3 , the average particle size is 0.2mm;

[0038] The density of crumb rubber (CR) is 2.65 g / cm 3 , the average particle size is 0.32mm;

[0039] The length of PE fiber (UHMWPE fiber) is 18 mm, the diameter is 24 μm, and the density is 0.97 g / cm 3 , tensile strength is 3000MPa, elastic modulus is 116GPa, and elongation is 1~3%;

[0040] The length of PP fiber is 18 mm, the diameter is 112 μm, and the density is 0.91 g / cm 3 , tensile strength is 400MPa, elastic modulus is 3.8GPa, and elongation is 26.7%;

[0041] The purity of NaOH solid is not less than 96%, and every 100 parts of sodium hydroxide solution contains 56 parts of sodium hydroxide solid;

[0042] The mass fractions of Na2O, SiO2 and H2O in water glass (Na2SiO3 solution) are 13.75%, 29.99% and 56.26% respectively, that is, every 100 parts of water glass contains 13.75 parts of sodium oxide, 29.99 parts of silicon dioxide and 56.26 parts of water;

[0043] The average particle size of fine sand (FS) is 0.120 mm, Dx(50)=0.107 mm;

[0044] The average particle size of medium sand (MS) is 0.400mm, Dx(50)=0.396mm.

[0045] Dx(50) in the fine sand and medium sand parameters refers to the median particle size, which is a way to measure the particle size distribution. It is also often written as D50, which refers to the particle size at which the cumulative percentage in the cumulative particle size distribution curve reaches 50%, that is, half of the particles have diameters smaller than this value, and the other half are larger than this value.

[0046] Figure 1 It is a schematic diagram of the preparation process of the self-healing high-toughness concrete of the present invention.

[0047] Figure 3 It is the particle size distribution curve diagram of the raw materials used in the present invention.

[0048] The preparation method of self-healing high-toughness concrete comprises the following steps:

[0049] S1. Mix blast furnace slag, fly ash and silica fume, add the obtained precursor powder mixture into a planetary mixer, and stir at a low speed (75 rpm) for 3 minutes to mix evenly;

[0050] S2, add medium sand, fine sand and crushed rubber, and continue stirring at low speed (75rpm) for 3min;

[0051] S3, add 14 mol / L sodium hydroxide solution, water glass and water, and stir at high speed (135 rpm) for 1 min;

[0052] S4. After adjusting the stirring speed to 75 rpm, add PE fiber and PP fiber, and then stir at high speed (135 rpm) for 3 minutes until the fibers are fully dispersed to obtain self-healing high-toughness concrete.

[0053] The raw material ratios of Examples 1 to 5 and Comparative Examples 1 to 2 are shown in Table 1.

[0054] Table 1

[0055]

[0056] Test example

[0057] The concrete prepared in Examples 1 to 5 and Comparative Examples 1 to 2 was prepared into cubes and dog bone specimens with dimensions as follows: Figure 2 As shown (unit: mm), the mixed concrete was quickly poured into the mold, and a vibration table was used to vibrate the specimen to eliminate the bubbles inside the specimen and make it dense. At the same time, the fluidity test was completed, and the specimen was covered with a film to prevent moisture evaporation. After curing for 24 hours in an indoor environment (temperature 25°C, humidity 55%), the specimen was demoulded and cured normally for 28 days in a closed environment (temperature 20°C, humidity 65%). After the curing was completed, the mechanical properties test was carried out.

[0058] The test specimens of Examples 1 to 5 and Comparative Examples 1 to 2 were subjected to axial tensile tests (tensile strength and peak tensile strain) and axial compressive tests (compressive strength). The test results are shown in Table 2 (the standard deviation of the results is in brackets).

[0059] The compressive strength of the cube specimen is tested according to the "Standard for Test Methods of Mechanical Properties of Ordinary Concrete" GB / 50081-2002, and is obtained by the cube compression test. The compressive strength of a 50mm×50mm×50mm cube is measured using a YAW-5000 microcomputer-controlled electro-hydraulic servo pressure testing machine MATEST material testing machine with a loading rate of 1800N / s. The compressive strength is calculated as follows: σm=F / A, where F is the force value recorded by the test machine and A is the cross-sectional area under load.

[0060] The axial tensile test was carried out using a dog bone specimen according to the JSCE specification, and was loaded using an electronic universal testing machine. The loading method was displacement control mode for tensioning, and the loading rate was 0.5 mm / min. Two symmetrical displacement gauges were used to measure the axial strain in the 80 mm area in the middle of the specimen, and the stress sensor and displacement gauge were combined to assist in data collection.

[0061] Table 2

[0062]

[0063] The test specimens of Examples 1 to 5 and Comparative Examples 1 to 2 were subjected to crack width detection test (average crack width / overall repair rate) and freeze-thaw test (mass loss rate) test:

[0064] The dog bone specimens were pre-damaged and pre-loaded using a universal testing machine. The load level was controlled to be no more than 60% of its compressive strength. The damage was pre-damaged by repeated loading in the vertical and horizontal directions. Every 3 to 5 loading processes, the ultrasonic detector was used to test the wave velocity of the damaged specimens. The damage degree of the concrete specimens was calculated (M is the damage degree of concrete, V1 is the wave velocity of the specimen before prefabrication damage, and V2 is the wave velocity of the specimen after prefabrication damage). By adjusting the load size and the number of loading times, the damage degree of the specimens was finally distributed between 0.2 and 0.3. Then 25 cracks of different widths were marked and regarded as crack observation points. The residual widths of the 25 crack points of different widths were tested again at the repair and curing age of 0d, 7d, 14d, and 28d, and the overall repair rate was calculated. The results are shown in Tables 3 and Figure 4 shown.

[0065] Figure 4 Schematic diagram of the crack width and 28-day overall repair rate of the specimens of Examples 1 to 5 at different curing times.

[0066] After 28 days of curing, the damaged specimens were subjected to freeze-thaw cycle treatment. According to the "quick freezing method" in the "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete" (GB / T50082-2009), the specimens were subjected to rapid freeze-thaw treatment. Before the freeze-thaw test, the specimens were placed in a vacuum saturated device for saturation treatment. After the saturation, the specimens were placed in a freeze-thaw box. The single freeze-thaw action time cycle was 4h. During the freezing process, the center temperature of the specimen was controlled at -18±2℃, and during the thawing process, the center temperature of the specimen was controlled at 5±2℃. The number of freeze-thaw cycles for each group of concrete specimens was 50, and their mass loss rates were measured respectively. The results are shown in Table 3.

[0067] Table 3

[0068]

[0069] As can be seen from Tables 2 and 3, Example 4 has the best tensile strength, and Example 3 has excellent compressive strength, average crack width, 28d total repair rate, and mass loss rate measured after freeze-thaw test. It can be seen that under the mix ratio of 900 parts of the total amount of precursor, the tensile strength of the concrete can reach more than 8.9Mpa, the compressive strength can reach more than 100Mpa, the 28-day concrete self-healing rate can reach 98%, and the mass loss rate after 50 freeze-thaw cycles is only 0.66%.

[0070] The mass loss rate is also one of the factors for judging the self-healing ability. The lower the mass loss rate, the smaller the crack width after repair and the better the anti-seepage performance. The materials in different embodiments and comparative examples have different compressive strengths and different initial crack widths after prefabricated damage. The small initial crack width can reflect that the compressive strength of this type of concrete is high, and the crack repair rate can reflect the self-healing ability of the concrete.

[0071] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.

[0072] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A self-healing high-toughness concrete, characterized in that: The raw materials include, by mass: 700-1100 parts of geopolymer precursor, 28.5 parts of sodium hydroxide solution, 306.6 parts of water glass, 543 parts of medium sand, 362 parts of fine sand, 95 parts of crushed rubber, 17 parts of PE fiber, 2.4 parts of PP fiber and 117.1 parts of water; The geopolymer precursor comprises blast furnace slag, fly ash and silica fume in a mass ratio of (530-850):(120-210):(30-60); The concentration of the sodium hydroxide solution is 14 mol / L.

2. The self-healing high-toughness concrete according to claim 1, characterized in that: The average particle size of the crumb rubber is 0.32 mm and the density is 2.65 g / cm 3 and / or, The average particle size of the fine sand is 0.12 mm, Dx(50)=0.107 mm; and / or, The average particle size of the medium sand is 0.40 mm, and Dx(50)=0.396 mm.

3. The self-healing high-toughness concrete according to claim 1, characterized in that: The mass fraction of Na2O in the water glass is 13.75%, the mass fraction of SiO2 is 29.99%, and the mass fraction of H2O is 56.26%.

4. The self-healing high-toughness concrete according to claim 1, characterized in that: The PE fiber has a length of 18 mm, a diameter of 24 μm, and a density of 0.97 g / cm 3 , tensile strength of 3000MPa, elastic modulus of 116GPa, elongation of 1~3%; and / or, The PP fiber has a length of 18 mm, a diameter of 112 μm, and a density of 0.91 g / cm 3 , the tensile strength is 400MPa, the elastic modulus is 3.8GPa, and the elongation is 26.7%.

5. The self-healing high-toughness concrete according to claim 1, characterized in that: The fly ash is Class F fly ash; and / or, The specific gravity of blast furnace slag is 2.88 g / cm 3 , the fineness value is 3800 cm 2 / g; and / or, The specific gravity of silica fume is 2.30 g / cm 3 , the average particle size is 0.2mm.

6. A method for preparing the self-healing high-toughness concrete according to any one of claims 1 to 5, characterized in that the steps include: After fly ash, blast furnace slag and silica fume are evenly mixed, crushed rubber, medium sand and fine sand are added and stirred evenly, then sodium hydroxide solution, water glass and water are added and stirred evenly, and finally PE fiber and PP fiber are added and stirred evenly to obtain the self-healing high-toughness concrete.